2010
DOI: 10.1590/s0074-02762010000500003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of Enterococcus faecalis CECT7121 on Toxocara canis

Abstract: The aim of the present paper was to evaluate the larvicidal effect of Enterococcus faecalis CECT7121 (Ef7121) on the Toxocara canis cycle both in vitro and in vivo. For the in vitro experiments, T. canis larvae were incubated with the supernatants of Ef7121 (EI) and mutant Ef7121 (EIm), in a pre-culture of Ef7121 (EII) and in a fresh culture with Ef7121 (EIII) and the Ef7121 mutant strain (EIIIm). The viability of the larvae was calculated after a 48 h incubation. A significant reduction of the viability of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…Reduction of worm burden was reported in mice infected with Trichinella spiralis 3,4,25 and Toxocara canis 2,7 . The failure of probiotics in affecting parasite load was reported in rats 12 and mice 33 infected with T. spiralis , and finally, an enhancement of mice susceptibility to Trichuris muris was attributed to Lactobacillus casei administration 11 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reduction of worm burden was reported in mice infected with Trichinella spiralis 3,4,25 and Toxocara canis 2,7 . The failure of probiotics in affecting parasite load was reported in rats 12 and mice 33 infected with T. spiralis , and finally, an enhancement of mice susceptibility to Trichuris muris was attributed to Lactobacillus casei administration 11 .…”
Section: Discussionmentioning
confidence: 96%
“…Studies on probiotics have revealed that these microorganisms contribute to host defense by reinforcing non-immunological responses and stimulating both specific and non-specific host immunity 14 . Probiotic bacteria have successfully been tested in intestinal protozoan and helmintic infections such as cryptosporidiosis 29 , giardiasis 6 , coccidiosis 9 , trichinellosis 3 and toxocariasis 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Also Enterococcus faecalis CECT7121, a probiotic with inhibitory activity against Gram-positive and Gram-negative bacteria, possesses in vitro and in vivo larvicidal activity determining up to a 90% reduction of the number of Toxocara canis larvae in liver and lungs of laboratory mice (Basualdo et al, 2007; Chiodo et al, 2010). Zymomonas mobilis , a bacterium producer of bioethanol, was reported to provide over 60% protection from the infection of S. mansoni in mice (Santos Jde et al, 2004).…”
Section: Probiotics Against Parasitesmentioning
confidence: 99%
“…There was no significant difference between the groups ( p > 0.05)Group104 105 106 107 Overall percentage S. boulardii 97.497.198.997.097.6 B. cereus var toyoi96.896.194.995.195.7 …”
mentioning
confidence: 94%
“…S. boulardii or B. cereus var. toyoi probiotics were then added in triplicate, at concentrations of 1.104, 1.105, 1.106 and 1.107 CFU/hole. The RPMI 1640 has been used and works with these probiotics6 19 and this medium with antibiotics was checked and did not inhibit the probiotics in the concentrations used.…”
mentioning
confidence: 99%